Psychological Description of Students in the Learning Process During Pandemic Covid-19 - Uswatun Hasanah; Ludiana Ludiana; Immawati Immawati; Livana PH (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
College students are vulnerable to experiencing psychosocial problems. Psychological stressors cause changes in a person's life so they are forced to adapt or cope with stressors that arise. . Changes in learning methods become one of the triggers for psychological changes, one of which is anxiety. Anxiety affects student learning outcomes, because it tends to produce confusion and distortion of perception. Prolonged anxiety that occurs continuously can cause stress that interferes with daily activities. If not resolved can lead to more serious psychological problems such as depression. Student anxiety, stress and depression are further enhanced by the existence of the Covid-19 pandemic with online learning methods. The study aims to determine the level of student anxiety in the learning process during the Covid-19 pandemic. This research is a quantitative research with a descriptive analytic approach. The research sample was 190 college students, the study was conducted in May 2020 on the students of Akper Dharma Wacana. . The sampling technique used is total sampling.The research instrument used the DASS-21 questionnaire. Data were analyzed univariately with a frequency distribution. The results of the study found that the majority of psychological problems experienced by student in the online learning process are anxiety, A total of 79 students experienced mild anxiety, 23 students experienced mild stress and 7 experienced mild depression.